Ghost citizens Jewish return to a postwar city - Krzyżanowski, Łukasz (Harvard University Press, 2020)
"Few Polish Holocaust survivors went home after liberation. Lukasz KrzyzÌ⁷anowski recounts the story of a group who did-the returnees of Radom. Bureaucrats tried to hold back their property and possessions to prop up the ruined state. And the returnees faced pogroms and even gangs of fellow Jews. Against it all, they struggled to rebuild their lives"--